EFFECT OF DIPPING SOLDERING ON THICKNESS AND INTERMETALLIC COMPOUND MORPHOLOGY BETWEEN Sn-3.0Cu LEAD-FREE SOLDER AND COPPER SUBSTRATE - Mookam, Niwat; Kanlayasiri, Kannachai (My University, 2022)
The thickness and morphology of intermetallic compounds formed between Sn-3.0Cu lead-free solder and the copper substrate were investigated. In the experiment, the dipping soldering was performed at 350°C using Sn-3.0Cu lead-free solder for various dipping time lengths of 5, 10, 20, 50, 75 and 100s, respectively. The results indicated that η- Cu6Sn5 intermetallic phase was found to exist between the lead-free solder and the copper substrate. The formation of an ε-Cu3Sn particles on the η- Cu6Sn5 surface and grain boundary was found only when the substrate was soldered for 75 and 100s. The long soldering time and formation of ε-Cu3Sn particles resulted in the morphology of the η- Cu6Sn5 IMC changed from scallop shape to more round. Nevertheless, the thickness and morphology of intermetallic compounds was also found to be influenced by the diffusion controlled process.
Keywords: Dipping soldering; Intermetallic compound (IMC); Morphology; Sn-3.0Cu solder